İNGİLTERE BAŞBAKANI DAVID LLOYD GEORGE'UN BİRİNCİ DÜNYA SAVAŞI ANILARI VE OSMANLI İMPARATORLUĞU'NA DAİR DÜŞÜNCELERİ - (:unkn) unknown (My University, 2016)
Tarihsel olayları anlamak için incelenen dönemin siyasi aktörlerini çalışmak ve onların anılarından  istifade  ederek  günün  olaylarını  açıklamak,  tarihçiler  için  vazgeçilmez  bir yöntemdir. Bu metinde, uzun yıllar İngiliz parlamentosunda görev yapmış, 1916-1922 arasında da  başbakanlık  görevini  üstlenmiş  olan  David  Lloyd  George  ve  anıları  çalışılmıştır.  Metin, George'un, basbakanlıgı döneminde uyguladığı ve daha sonra da anılarında bahsettiği Osmanlı İmparatorluğu  ile  ilgili  dış  politikalarına  odaklanmıstır.  Bu  politikaların  çoğunun,  George'un Osmanlı'ya  karşı  olan  ön  yargılı  tutumundan  kaynaklandığı  gösterilmeye  çalışılmıştır.  Bu çalışmada,  George'un  başbakanlıktan  ayrıldıktan  sonra  yazmış  olduğu  anıları,  ne  zaman tamamlanıp  basıldığı  ve  içeriği  anlatılmıştır.  Anıların  basılmasından  sonra  gerek  o  zamanın siyasi  aktörlerinden,  gerekse  halktan  alınan  tepkilerden  bahsedilmiştir.  Bu  makalede, George'un  1938  yılında  tekrar  elden  geçirilip  iki  cilt  halinde  yayımlanmış  olan  Anılar  isimli kitabı esas alınmıştır.

Studying  the  leading  actors  of  the  periods  and  explaining  the  events concerning the related periods through the political actors' memoirs are indispensable methods for historians in order to understand historical events. In this article, Lloyd George, who served in the British Parliament for a long time and  worked as the Prime Minister between 1916 and 1922, and his memoirs were studied. This article focuses on the applications of George's foreign policy related to The Ottoman Empire and then, his memoirs in this context. It is also claimed that  most  of  his  foreign  policy  is  based  on  his  prejudice  against  The  Ottoman  Empire.  In  this study,  George's  memoirs,  which  he  wrote  after  he  had  quited  the  prime  ministry,  the  period when  these  memoirs  were  completed  and  the  content  of  them  were  presented.  After  these memoirs had been published, the reactions regarding these books from both political actors of the  term  and  the  public  were  also  told.  This  article  based  on  George's  memoirs,  which  were revised and published as two volumes in 1938.
THE MEMOIRS OF DAVID LLOYD GEORGE, THE BRITISH PRIME MINISTER, CONCERNING WORLD WAR I AND HIS THOUGHTS REGARDING THE OTTOMAN EMPIRE'S PARTICIPATION IN THE WAR
Keywords: Tarih